2017
DOI: 10.1002/14651858.cd012707
|View full text |Cite
|
Sign up to set email alerts
|

Adult patient access to electronic health records

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To assess the effects of providing access to electronic health records (EHR) alone or with additional functionalities to adult patients on a range of patient, patient-provider and health resource consumption outcomes.The secondary objective is to compare the effects of providing EHR access alone, compared with EHR access with additional functionalities, to adult patients and to assess whether the effects differ among patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…", and "Great way to contact my Dr or access my info". This matches the findings by Ammenwerth, Schnell-Inderst [19] who stated that access to information is one facet of patient satisfaction. The users also reported the ability to check test results as an important feature of MyChart.…”
Section: Access Medical Recordssupporting
confidence: 90%
See 2 more Smart Citations
“…", and "Great way to contact my Dr or access my info". This matches the findings by Ammenwerth, Schnell-Inderst [19] who stated that access to information is one facet of patient satisfaction. The users also reported the ability to check test results as an important feature of MyChart.…”
Section: Access Medical Recordssupporting
confidence: 90%
“…Patient portals can lead to improvements in clinical outcomes, patient behavior, and experiences Sorondo, et al [36] Assess whether patient portals influence patients' ability for selfmanagement, improve overall health, and reduce healthcare utilization Quasiexperimental prepost study design Portals may improve access to providers and health data that lead to improvements in patients' functional status and reduce high-cost healthcare utilization, but it does not improve self-efficacy, the perception of health state, or experience with primary care practices Kruse, et al [18] Summarize results the effect of patient portals on quality, or chroniccondition outcomes, and its implications for Meaningful Use Systematic literature review Very few studies associated use of the patient portal, or its features, to improved outcomes. Other studies reported improvements in medication adherence, disease awareness, selfmanagement of disease, a decrease of office visits, and increase in quality regarding patient satisfaction and customer retention Ammenwerth, et al [19] Address the impact of electronic patient portals on patient care…”
Section: Realist Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, at the moment, a Cochrane review was started by our group to systematically evaluate the most recent evidence on the impact of patient portals on patient empowerment [19]. A still running systematic literature search identified only 12 randomized studies, most of them from the United States.…”
Section: Patient Portals and Patient Empowermentmentioning
confidence: 99%
“…Although one might expect online access to increase patient activation and thus improve health outcomes, less activated patients may be less likely to take advantage of online access [39] thus potentially exacerbating health inequalities. Disappointingly, reviews of the literature to date reveal a lack of evidence for the impact of online access on health outcomes [31] [32], although an up to date systematic review is underway [40].…”
Section: Challenges and Potential Negative Consequencesmentioning
confidence: 99%